Studies on the Biotransformation of Veratric Acid, a Human Metabolite of Mebeverine, by Using the Incubated Hen’s Egg - Kiep, L.; Göhl, M.; Schmidt, J.; Seifert, K. (Drug Research, 2015)
Metabolism studies with selected test substances have shown that a model on the basis of the incubated hen’s egg is suitable as a supplement to animal experimentation. Because of its 3,4-dimethoxyphenyl structure veratric acid (3,4-dimethoxybenzoic acid), a known human metabolite of mebeverine, was chosen as model substance for the present investigations and the parent compound as well as 4-hydroxy-3-methoxybenzoic acid were identified as main metabolites. The absence of 3-hydroxy-4-methoxybenzoic acid lets conclude that the O-demethylation takes place exclusively at the p-methoxyl function. In addition, 3,3’,4,4’-tetramethoxy-l-ornithuric acid (2,5-bis-(3,4-dimethoxybenzoylamino)pentanoic acid) and its O-desmethyl derivative could be characterized as further metabolites. So far an amino acid conjugate has not been described after veratric acid administration in a vertebrate. There were no indications for the appearance of 3,4-dihydroxybenzoic acid in the veratric acid metabolism. This was confirmed by corresponding studies having the isomeric guaiacol acids as precursor. Furthermore, it could be proved that in ovo the O-methylation of 3,4-dihydroxybenzoic acid occurs regioselective at the m-hydroxyl group. The results which broaden the knowledge on the metabolic fate of veratric acid are discussed in comparison with those in mammals. The metabolites were identified by GC-MS, ESI-HRMS and LC/ESI-MS/MS. The structure of the synthesized reference substance was confirmed by MS, 1H and 13C NMR spectral data.
Keywords: complementary method to animal testing; 3,4-dimethoxyphenyl moiety; guaiacol acids; O-demethylation; O-methylation; amino acid conjugation